Evolution of structural and magnetic properties of Co-doped TiO2 thin films irradiated with 100MeV Ag7+ ions - Mohanty P.; Singh V.P.; Mishra N.C.; Ojha S.; Kanjilal D.; Rath C. (My University, 2025)
In continuation to our earlier studies where we have shown room temperature ferromagnetism observed in TiO2 and Co-doped TiO2 (CTO) thin films independent of their phase (Mohanty et al 2012 J. Phys. D: Appl. Phys. 45 325301), here the modifications in structure and magnetic properties in CTO thin films using 100MeV Ag7+ ion irradiation are reported. Owing to the important role of defects in tailoring the magnetic properties of the material, we vary the ion fluence from 5×1011 to 1×1012ionscm-2 to create post-deposition defects. While the film deposited under 0.1mTorr oxygen partial pressure retains its crystallinity showing radiation-resistant behaviour even at a fluence of 1×1012ionscm-2, films deposited under 1 to 300mTorr oxygen partial pressure becomes almost amorphous at the same fluence. Using Poisson's law, the diameter of the amorphized region surrounding the ion path is calculated to be ∼4.2nm from the x-ray diffraction peak intensity ((1 1 0) for rutile phase) as a function of ion fluence. The saturation magnetization (Ms) decreases exponentially similar to the decrease in x-ray peak intensity with fluence, indicating magnetic disordered region surrounding the ion path. The diameter of the magnetic disordered region is found to be ∼6.6nm which is larger than the diameter of the amorphized latent track. Therefore, it is confirmed that swift heavy ion irradiation induces a more significant magnetic disorder than the structural disorder. © 2014 IOP Publishing Ltd.